What price a living wage? Understanding the impact of a living wage on firm-level wage bills - Pennycook, Matthew (London, 2012)
"The report concludes that for many, especially in banking, IT and construction, the average upfront wage costs are affordable, representing less than a 1 per cent increase. In other industries, such as retail and hospitality, where the proportion of lower-paid jobs is higher, the upfront costs would be higher, at between 4.7 and 6.2 per cent. So for these firms the report recommends a phased introduction, starting with a move to pay 90 per cent of the living wage.